Augmented and Virtual Reality in Medical Treatment: Machine Learning’s Transformative Impact - Sanjeev Gour; Manish Joshi; Hemant Pal; A.R. Qureshi (Science and Technology: Developments and Applications Vol. 1, 2024)
This chapter explores the transformative role of machine learning techniques in advancing medical treatment assistance, particularly through the integration of augmented reality (AR) and virtual reality (VR) technologies. By bridging the domains of artificial intelligence, immersive technologies, and healthcare, this study explores how the synergy between machine learning, AR, and VR has the potential to redefine medical diagnostics, surgical precision, patient care, and professional medical training. The chapter presents a comprehensive analysis of recent technological advancements, emphasizing the application of machine learning algorithms for real-time data analysis, predictive modeling, and decision-making in AR/VR-enabled environments. It highlights the role of AR in overlaying critical diagnostic information and VR in simulating realistic scenarios for training and treatment planning. Through case studies and emerging trends, the research showcases the effectiveness of these combined technologies in achieving more accurate diagnoses, facilitating minimally invasive surgeries, optimizing patient rehabilitation, and enhancing the experiential learning of medical professionals. Additionally, this study discusses the implications of integrating machine learning in AR/VR systems, such as improved personalization of patient care, reduced medical errors, and the development of intelligent, adaptive healthcare tools. By addressing the challenges and opportunities in this interdisciplinary field, the chapter aims to underscore the pivotal contributions of machine learning-powered AR and VR technologies in revolutionizing modern healthcare practices and shaping the future of medical treatment assistance.